2010
DOI: 10.1080/17440570903475683
|View full text |Cite
|
Sign up to set email alerts
|

Farmers, factories and funds: organised crime and illicit drugs cultivation within the British Vietnamese community

Abstract: This article explores the growth of organised crime within the Vietnamese community with particular reference to the cultivation of cannabis, money laundering and the smuggling or trafficking of children. The article begins by exploring the history and diversity of the 'Vietnamese community' in the United Kingdom and the role of Vietnamese culture in shaping their criminal enterprises. It then draws on research involving two sets of qualitative data: one set is based on 45 interviews with law enforcement perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 3 publications
(3 reference statements)
0
17
0
Order By: Relevance
“…In the majority of the criminological studies on this topic, the focus is on specific criminal activities such as illegal migration (Okólski 1999), the trade in drugs (Trung 1998;Silverstone & Savage 2010;Schoenmakers et al 2013), the trade in other illegal commodities (von Lampe 1999), delinquency as a general phenomenon (zhou & bankston III 2006) and Vietnamese gangs (English 1995;Kleinknecht 1996;Du Phuoc Long & Richard 1997;Nye 2006). Vietnamese criminal networks are discussed more or less marginally in this context (Cross 1989).…”
Section: Information Sources and Research Methodsmentioning
confidence: 98%
“…In the majority of the criminological studies on this topic, the focus is on specific criminal activities such as illegal migration (Okólski 1999), the trade in drugs (Trung 1998;Silverstone & Savage 2010;Schoenmakers et al 2013), the trade in other illegal commodities (von Lampe 1999), delinquency as a general phenomenon (zhou & bankston III 2006) and Vietnamese gangs (English 1995;Kleinknecht 1996;Du Phuoc Long & Richard 1997;Nye 2006). Vietnamese criminal networks are discussed more or less marginally in this context (Cross 1989).…”
Section: Information Sources and Research Methodsmentioning
confidence: 98%
“…Nonetheless, it is important to acknowledge that it is the modern technologies that underpin globalisation, from air travel to the Internet, the mobile phone and the satellite navigation systems, which have allowed Vietnamese networks in particular to dominate domestic cannabis cultivation (Silverstone and Savage, 2010). From learning their skills in British Columbia they have moved effortlessly to the suburban terraced houses of the UK, aided by Internet discussion boards giving detailed instructions of how to cultivate the most potent cannabis, horticultural equipment advertised on the web or via Ebay, satellite navigation systems and pay as you go mobile phones which enable those new to the UK to navigate their way through unknown streets and to control numerous cultivation sites.…”
Section: The Growth Of Organised Crime?mentioning
confidence: 99%
“…The Vietnamese population in the UK was enlarged by the second major migration wave which happened in the early 1990s. This phase consisted of undocumented Vietnamese migrants who were previously residing in the former Soviet Union, as well as other parts of Eastern Europe (Silverstone and Savage 2010). This also included a number of Vietnamese guest workers in former East Germany (IRASEC and France terre d'asile, 2017).…”
Section: The Vietnamese Immigrants In Germany and The Uk Different Wamentioning
confidence: 99%
“…Finally, much like the situation in Germany, the third migration wave from Vietnam to the UK has also been known as the 'new arrivals' who illegally migrated due to economic reasons. It first included individuals smuggled from Northern provinces of Vietnam (Silverstone and Savage 2010) and then a further migration stream starting from the late 2000s from the same North Central Coast provinces (IRASEC and France terre d'asile, 2017). A study by Sims (2010) reported an estimate of some 20.000 undocumented Vietnamese living in the UK in 2007.…”
Section: The Vietnamese Immigrants In Germany and The Uk Different Wamentioning
confidence: 99%